People power popular sovereignty from Machiavelli to modernity - Ingram, Robert G.; Barker, Chris (Christopher James) (Manchester University Press, 2022)
This book analyses popular sovereignty, one of the fundamental features of modern politics and history. It critically engages with the key thinkers responsible for creating and criticizing popular sovereignty and covers topics such as war, finance, legislation, revolution, religion and political ideology.